(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the importance, possibilities and application in modern pedagogical practice of organizing interactive education based on digital technologies. Today, the enrichment of the educational process with digital technologies encourages students to learn in a more active and motivated state. The article analyzes the impact of interactive educational platforms on pedagogical approaches, the role of digital tools in the development of students’ abilities, and the effectiveness of interactive methods. The interaction between teachers and students using digital technologies, the development of distance learning, and the possibilities of an individual approach through online platforms are considered. Such interactive educational methods support students’ independent thinking, creativity, and self-development. The article also emphasizes the need to develop methodological skills and pedagogical competencies necessary for the successful use of digital technologies in education